Urgensi Peserta Didik MA Al-Bairuny Jombang Terhadap Materi Nahwu Berbasis Konten Instagram - Maulidiyah, Lailil; Sulaikho, Siti (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Nahwu material tends to be difficult, making students feel bored quickly and less interested in learning it more deeply. The thing that needs to be considered is variation in learning. One of the variations in learning is using social media based on Instagram content so that students can easily understand and make the learning atmosphere interesting. This study aims to reveal the needs and improvement of students towards instagram content-based nahwu. In addition, it is intended to show that Instagram, which is usually only used to share photos or videos, can be effectively used as a learning tool to show. The research method used in this study is mix method sequential exploratory. The data collection technique used interviews and pre-test and posttest, The interview involved 5 (five) participants with the criteria of class XII who had studied nahwu material, as well as post-test and pre-test participants totaling 20 students. The data analysis technique uses the miles and huberman model, namely data collection, data reduction, data presentation, and conclusion drawing/verification. The results of this study indicate that the urgency of students to instagram content-based nahwu material is needed and the use of learning content through Instagram social media in class XII IPA 1 students can be declared effective in improving students' ability to nahwu subjects. This is because the display of nahwu content on Instagram can help make the learning process more interesting so that it can be easily understood. Therefore, there is a need for media to convey nahwu material.